Coexistence States of a Strongly Coupled Prey-predator Model (Journal of Partial Differential Equations, 2005)
This paper is concerned with a strongly coupled prey-predator model with homogeneous Dirichlet boundary conditions. The existence and uniqueness of coexistence states are discussed.